Endoscopic sclerotherapy in the management of nonvariceal upper gastrointestinal bleeding - Kadir AKSÖZ; Belkıs ÜNSAL; G. ÖNDER; Nafi YAZICIOĞLU; Sadun KOŞAY (Turkish Journal of Gastroenterology, 2020)
-